Utilization of biscuit waste in the ration of growing goat bucks - BAKSHI, M P S; SAINI, J K; WADHWA, M (The Indian Journal of Animal Sciences, 2022)
A feeding trial of 106 days was conducted to assess the impact of incorporating biscuit waste in the iso-nitrogenous and iso-caloric TMRs on the in vitro nutrient utilization and on the performance of growing goat bucks. The biscuit waste is an excellent source of EE (13.70%), starch (44.23%) and moderate source of CP (7.99%). The in vitro gas production studies revealed that the NGP, total and individual VFAs concentration improved significantly in TMR in which concentrate mixture contained biscuit waste. The DM intake, digestibility of the nutrients and N-retention was improved significantly in growing bucks fed TMR containing biscuit waste. The rumen studies revealed that bacterial and total protozoal population decreased, while fungal population in the rumen increased significantly in the bucks fed diet containing biscuit waste. The bacterial, fungal and total protozoal population was higher in the strained rumen liquor before feeding as compared to after feeding. The total and individual VFAs concentration was comparable in both the TMRs. The results conclusivelyrevealed that biscuit waste a rich source of nutrients can be incorporated in the concentrate mixture at 30% on DM basis without affecting palatability, nutrient utilization and body weight gain in growing goat bucks.